2020
DOI: 10.1371/journal.pone.0228306
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity and structural analysis of trial spinal cord stimulation responders in failed back surgery syndrome

Abstract: Background Chronic pain has been associated with alterations in brain structure and function that appear dependent on pain phenotype. Functional connectivity (FC) data on chronic back pain (CBP) is limited and based on heterogeneous pain populations. We hypothesize that failed back surgery syndrome (FBSS) patients being considered for spinal cord stimulation (SCS) therapy have altered resting state (RS) FC cross-network patterns that 1) specifically involve emotion and reward/aversion functions and 2) are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 40 publications
4
26
0
Order By: Relevance
“…For homogeneous cohorts, studies that focused on the FBSS population revealed similar alterations in cortical networks (i.e., decreased FC within the DMN, and increased FC between the DMN and salience, central executive, and sensorimotor networks) compared to healthy controls (Kornelsen et al, 2013;Kolesar et al, 2017;Pahapill et al, 2020). Moreover, Pahapill et al reported decreased FC between the striatum and other networks, decreased FC between the PAG and DMN, and increased FC between the PAG and sensorimotor networks (Pahapill et al, 2020). There is shortage of rs-fMRI studies that specifically exams homogeneous groups, hence it remains unclear whether neuropathic chronic pain express differentiable connectivity patterns from nociceptive chronic pain patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For homogeneous cohorts, studies that focused on the FBSS population revealed similar alterations in cortical networks (i.e., decreased FC within the DMN, and increased FC between the DMN and salience, central executive, and sensorimotor networks) compared to healthy controls (Kornelsen et al, 2013;Kolesar et al, 2017;Pahapill et al, 2020). Moreover, Pahapill et al reported decreased FC between the striatum and other networks, decreased FC between the PAG and DMN, and increased FC between the PAG and sensorimotor networks (Pahapill et al, 2020). There is shortage of rs-fMRI studies that specifically exams homogeneous groups, hence it remains unclear whether neuropathic chronic pain express differentiable connectivity patterns from nociceptive chronic pain patients.…”
Section: Discussionmentioning
confidence: 97%
“…Particularly, medial prefrontal cortex (mPFC) seems playing an important role in cLBP (Baliki et al, 2011(Baliki et al, , 2014Yu et al, 2014). The lack of brain activities in common noxious regions indicated that chronic pain may not be caused by nociceptive process, but rather associated with emotional and cognitive processes and potentiated through connectivity of these regions (Ng et al, 2017;Pahapill et al, 2020). In addition, enhanced rsFC in cLBP were also observed in the sensorimotor networks (Mao et al, 2022a), visual networks (Shen et al, 2019;Lamichhane et al, 2021a,b), reward network (Yu et al, 2020), and DMN-PAG couplings (Yu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Functional MR (fMR) studies and morphometric MR studies have established that patients with chronic pain show functional and structural brain alterations 9 50 51. In patients with chronic lumbar pain, fMR reflects a lower activation of the prefrontal cortex and the nucleus accumbens, with connectivity between both, proportional to the chronicity of the lower back pain 9. Morphological changes had a negative correlation with the duration of the pain.…”
Section: Imaging Biomarkers In Patients With Neurostimulation Therapymentioning
confidence: 99%
“…MRI has established that patients with chronic pain present functional and structural brain alterations. From the analysis of the neural circuits involved in the integration of pain, predictive imaging biomarkers have been proposed, capable of determining the characteristics of patients that can predict the success of SCS implants 8 9. Recent literature shows changes in the relative expression of genes and proteins in peripheral blood mononuclear cells (PBMC) of patients with chronic pain treated with SCS, as potential biomarkers of the therapy outcome 10…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the large-diameter fibers in the dorsal columns is thought to inhibit pain transmission via gating within the dorsal horn (Zhang et al, 2014) (Yang et al, 2011) however, several studies suggest that additional segmental and supraspinal mechanisms are involved in EES-induced analgesia (Gilbert et al, 2022). Variations in the effect of EES to control pain can be attributed to multiple factors, such as initial placement or later migration of the electrode contacts, patient position, and the functional state of the neuronal circuitry (Mekhail et al, 2022) (Pahapill et al, 2020) (Dombovy-Johnson et al, 2022a). Although lead migration can be confirmed through clinical imaging, there is currently no clinically available method to detect and flag the possibility of lead migration for EES automatically and continuously which would allow for decreased loss of efficacy.…”
Section: Introductionmentioning
confidence: 99%